(untitled) (Bangladesh Journal of Pharmacology, 2016)
Since autoimmune diseases dramatically affect function of various tissues and organs in vivo, each integral organ of mouse has significant value in order to analyze the effect of any pharmaceuticals or test drugs to confirm their protective efficacy. Hence, this study reports step-by-step visual demonstration of isolation of various internal tissue organs such as liver, spleen, adipose tissue, muscles, and pancreas from mouse model which have significant contribution to design in-depth molecular level studies along with histomorphological evidences that may assist research to set innovative results at molecular level, thus may help to prove the efficacy of any test sample as a new drug of pharmaceutical importance. Video Clip of Methodology: Isolation of organs: 7 min 55 sec Full Screen Alternate